The importance of ultrasound examination in care of juvenile idiopathic arthritis patients: 9 months follow-up study - Snipaitiene, Ausra; Slegeryte, Andzelika; Uktveris, Rimantas; Sileikiene, Rima; Jakucionis, Paulius; Baranauskaite, Asta; Jankauskaite, Lina (Frontiers in Pediatrics, 2024)
Introduction:Juvenile idiopathic arthritis(JIA) is a group of rare musculoskeletal disorders with chronic inflammation of joints,typically manifesting before the age of 16 years.The assessment of disease activity remains pivotal in JIA treatment decisions, particularly during clinical remission.While musculoskeletal ultrasound(MSUS) has shown promise in detecting subclinical synovitis, longitudinal data on MSUS features in JIA remains limited.The aim of this study was to evaluate the prevalence of subclinical synovitis observed in MSUS over a follow-up period in JIA patients.Additionally, it sought to assess the consistency and correlation between clinical findings, standardized composite clinical score(JADAS10), and MSUS-detected synovitis during 9-months follow-up.Patients and methods: prospective single-center study was conducted, enrolling all consecutive JIA patients(excluding systemic JIA) seen at the study center in one year period.At three-months intervals over a 9-months period(M0,M3,M6 and M9),patients underwent clinical examination, laboratory tests, and MSUS assessment.Data on demographic characteristics, disease profile,and treatment were collected.Patients were categorized into active disease(ACT) or remission(REM) groups based on Wallace criteria and JADAS10 scores using previously validated thresholds.The ultrasound assessments adhered to the Outcome Measures in Rheumatology Clinical Trials(OMERACT) pediatric group,covering 40 joints,were performed by two ultrasonographers at every visit.Subclinical synovitis was defined as synovitis detected exclusively by MSUS.Spearman's correlation coefficients (rs) were used to evaluate the association between MSUS, clinical data, and outcome measures, such as active joint count(ACJ), patient's/parent's global assessment of disease activity(PaGA), physician's global assessment of disease activity(PhGA) and JADAS10.Results:subclinical synovitis was evident in 5.2% of all joints and in 80.6% of the patients at baseline.During the follow-up period, signs of subclinical synovitis decreased to 3.8% of joints, however, the proportion of affected patients remained high(67.7%), with the majority in REM group.Despite the consistent strong correlation between PaGA and PhGA throughout the study(rs>0.895; p<0.001), both measures displayed moderate(rs=0.647; p<0.001) to weak(rs=0.377; p=0.04) correlations with MSUS findings. Notably, PaGA remained significantly correlated with MSUS at the M9 visit(rs=0.377, p=0.04), while PhGA showed no correlation(p=0.094).The study results indicate the persistence of subclinical inflammation detected by MSUS in a significant proportion of JIA patients,even during clinical remission.Moreover, the findings suggest that conventional measurements of JIA activity may be insufficient for patients in clinical remission.